2010
DOI: 10.2193/2009-286
|View full text |Cite
|
Sign up to set email alerts
|

Bispectral Index Analysis of Opioid Immobilization of Rocky Mountain Elk

Abstract: We immobilized elk with either isoflurane to produce general anesthesia (control), 0.01 mg/kg carfentanil plus 0.1 mg/kg xylazine, or 0.25 mg/kg butorphanol plus 0.4 mg/kg azaperone plus 0.15 mg/kg medetomidine (BAM) and measured the bispectral index (BIS). The carfentanil-xylazine BIS (70.4 6 1.4) and the BAM BIS (60.2 6 1.5) were higher than the control BIS (47.2 6 4.1; P M 0.001). These data indicate that opioids produce neuroleptanalgesia and not general anesthesia or sedation, which explains observed elk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…That relatively little had been published on field use of BAM in large-bodied ungulates may have contributed to the disparity in perceptions. The dosage in one publication (e.g., 0.15 mg medetomidine/kg; Kreeger et al 2010) was similar to that originally reported in white-tailed deer (Odocoileus virginianus; Mich et al 2008), but was about twice the rate that we had been successfully using for elk field captures (0.04-0.08 mg medetomidine/kg; L.L.W. unpubl.).…”
supporting
confidence: 69%
See 1 more Smart Citation
“…That relatively little had been published on field use of BAM in large-bodied ungulates may have contributed to the disparity in perceptions. The dosage in one publication (e.g., 0.15 mg medetomidine/kg; Kreeger et al 2010) was similar to that originally reported in white-tailed deer (Odocoileus virginianus; Mich et al 2008), but was about twice the rate that we had been successfully using for elk field captures (0.04-0.08 mg medetomidine/kg; L.L.W. unpubl.).…”
supporting
confidence: 69%
“…A relatively new combination of sedatives, which includes butorphanol tartrate, azaperone tartrate, and medetomidine HCl (BAM; Wolfe et al 2008), has been used successfully to immobilize a variety of ruminant species, including elk (Kreeger et al 2010(Kreeger et al , 2012L.L.W. unpubl.).…”
mentioning
confidence: 99%
“…A major advantage of opioids for wildlife immobilization is the availability of specific antagonists. Opioids are neuroleptanalgesics characterized by spontaneous movements and responsiveness to noise, touch, and other stimulation, which indicate that they are not completely unconscious, a characteristic of general anesthesia (Kreeger et al 2010).…”
Section: Etorphinementioning
confidence: 99%